Accuracy analysis of the new artificial anatomical marker positioning method (shoulder-to-shoulder) in preventing leg length discrepancy in total hip arthroplasty - Ze-feng, Wang; Yang-zhen, Fang; Yong-qiang, Zheng; Zhen-yu, Lin; Liang, Lin; Xiao-feng, Liu; Chi, Zhang; Jin-shan, Zhang (Frontiers in Surgery, 2024)
ObjectiveBy comparing the hip arthroplasty parameters planned with the AIHIP three-dimensional simulation surgery system, this study analyzes the accuracy of the new femoral-side “shoulder-to-shoulder” artificial anatomical marker positioning method in femoral-side prosthesis implantation and the prevention of leg length discrepancy in hip arthroplasty.MethodsA retrospective collection of 47 patients who underwent initial total hip arthroplasty at our hospital from August 2020 to December 2022 and met the inclusion and exclusion criteria was used as the study subjects. The average age was 67.34 ± 10.86 years (32–80 years), including 17 males and 30 females; 25 cases on the left side and 22 cases on the right side. According to the Garden classification for fractures: 4 cases of type II, 4 cases of type III, and 21 cases of type IV; according to the ARCO staging for femoral head necrosis: 1 case of stage III and 6 cases of stage IV; according to the Crowe classification: 2 cases of type I and 3 cases of type II; according to the K-L grading: 2 cases of stage III and 4 cases of stage IV. The postoperative pelvic anteroposterior x-ray measurement parameters and prosthesis model results guided by the new “shoulder-to-shoulder” artificial anatomical marker positioning method (“shoulder-to-shoulder” group) were compared with the corresponding parameter results planned by the AIHIP three-dimensional simulation surgery system (AIHIP simulation surgery group). All postoperative pelvic anteroposterior x-ray measurement parameters were corrected according to the radiographic magnification, and the differences in bilateral lower limb length, tip-to-shoulder distance, and osteotomy distance between the two groups were compared. The paired t-test was used to compare the differences in bilateral lower limb length, tip-to-shoulder distance, and osteotomy distance; descriptive analysis was used to evaluate the consistency of prosthesis model matching.alpha = 0.05 (both sides).ResultsThe differences in bilateral lower limb length for the “shoulder-to-shoulder” group and the AIHIP simulation surgery group were 1.07 ± 1.18 mm and 1.28 ± 2.41 mm, respectively, with a difference of −0.28 ± 2.16 mm between the two groups. The paired t-test results showed no statistically significant difference (P = 0.508). The tip-to-shoulder distance and osteotomy distance for the “shoulder-to-shoulder” group were 15.93 ± 2.96 mm and 7.81 ± 2.73 mm, respectively, while the corresponding parameters for the AIHIP simulation surgery group were 17.70 ± 3.39 mm and 9.21 ± 4.05 mm. The differences in tip-to-shoulder distance and osteotomy distance between the “shoulder-to-shoulder” group and the AIHIP simulation surgery group were −1.78 ± 2.54 mm and −1.22 ± 3.17 mm, respectively. The paired t-test results showed statistically significant differences in the comparison of tip-to-shoulder distance and osteotomy distance between the two groups (both P < 0.01). The matching rates of acetabular and femoral prosthesis models were 91.48% and 95.74%, respectively.ConclusionThe new artificial anatomical marker positioning method (shoulder-to-shoulder) and the AIHIP three-dimensional simulation surgery method show good consistency in preventing leg length discrepancy in hip arthroplasty. This proves that using this method can accurately implant the femoral-side prosthesis during surgery and prevent postoperative leg length discrepancy.